(untitled) (International Journal of Engineering Management Science, 2024)
Imagine the convenience if we could control various devices in home/industry with one computer. The purpose of our project is the same and can be used to control the power of a printer, chargers and other electrical devices in the home. The circuit includes a inverter, IR transmitter, IR receiver, relay and relay control parts. We use the parallel port of the computer to control these devices.